Adropin- A Novel Biomarker of Heart Disease: A Systematic Review Article - Somaye YOSAEE; Sepideh SOLTANI; Eghbal SEKHAVATI; Shima JAZAYERI (Tehran University of Medical Sciences, 2016)
Background: Heart disease is one of the most common chronic disease and leading cause of morbidity and mortality worldwide. Adropin, a newly identified protein, is important for energy homeostasis and maintaining insulin sensitivity, and has been referred to as a novel regulator of endothelial cells. Endothelial dysfunction is a key early event in atherogenesis and onset of HD. Therefore, this review gives a systematic overview of studies investigating plasma adropin level in patient with heart disease. Methods: Data carried out in PubMed, Scopus, Web of Science, Embase, Google scholar and MEDLINE, from the earliest available online indexing year through 2015. The search restricted to studies conducted in humans. The keyword search was adropin to apply in title, abstract and keywords. References lists of all original published articles were scanned to find additional eligible studies. Results: Heart failure (HF), coronary atherosclerosis acute myocardial infarction and Cardiac Syndrome X (CSX) were type of heart disease acknowledged in this study. Majority of evidences introduced low adropin as an independent risk factor of heart disease. In a case-control study, the plasma level of adropin increased with the severity of HF. Conclusion: Adropinmay be a potential serum biomarker for early diagnosis of HD.